Educational Activity in the Development of a Growing Personality - Bekh, Ivan (Theoretical and Methodical Problems of Children and Youth Education, 2025)
Theoretical searches into the problems of education, currently being carried out, cover a wide range of aspects of the educational process. So far, priority has been given to age-differentiated content, developmental methods, and forms. At the same time, the educational process remained insufficiently conceptualized. It was assumed only as a subjective interaction between teachers and students without a detailed disclosure of the target stages, which sharply reduced its effectiveness. Moreover, problems arose with the organization of its real management. In the article, the educational process is considered as the unity of educational activity, which is implemented by the teacher, and educational activity (hereinafter referred to as “EA”), the subjects of which are the students. The main focus is on the EA. For greater logical orderliness of educational activity, it is traced in the main functional parameters. 1. The developmental function of the EA. The motives of such activity will be selfless devotion to the people, the Homeland, the state, and the desire to benefit the nation. 2. The sensory-cognitive function of the EA. The growing personality functions in the axiological sphere as an accumulator, carrier, and broadcaster of spiritual achievements. 3. The methodological function of the EA. Educational activity is developed as a meta-principle within the context of a corresponding project. 4. The dialogical function of the EA. This function promotes interpersonal openness, facilitating readiness to perceive judgments and emotional experiences related to specific relationships. 5. The psycho-optimizing function of the EA. It is associated with a reliance on positive emotions, such as joy, as an indicator of students’ internal well-being.